Isolated glucocorticoid deficiency: Genetic causes and animal models. Issue 189 (May 2019) - Maharaj, Avinaash; Maudhoo, Ashwini; Chan, Li F.; Novoselova, Tatiana; Prasad, Rathi; Metherell, Louise A.; Guasti, Leonardo
Highlights: The molecular basis of adrenal resistance to ACTH is heterogenous. Clinically, ACTH resistance manifests as ACTH excess in the setting of hypocortisolaemia. Genes whose mutations cause Familial Glucocorticoid Deficiency include MC2R, MRAP, and STAR . Genes involved in cellular redox balance, cholesterol synthesis and sphingolipid metabolism, have also been involved. Mouse models of FDG have been developed and they mimick, completely or only partially, the human phenotype. Abstract: Hereditary adrenocorticotropin (ACTH) resistance syndromes encompass the genetically heterogeneous isolated or Familial Glucocorticoid Deficiency (FGD) and the distinct clinical entity known as Triple A syndrome. The molecular basis of adrenal resistance to ACTH includes defects in ligand binding, MC2R/MRAP receptor trafficking, cellular redox balance, cholesterol synthesis and sphingolipid metabolism. Biochemically, this manifests as ACTH excess in the setting of hypocortisolaemia. Triple A syndrome is an inherited condition involving a tetrad of adrenal insufficiency, achalasia, alacrima and neuropathy. FGD is an autosomal recessive condition characterized by the presence of isolated glucocorticoid deficiency, classically in the setting of preserved mineralocorticoid secretion. Primarily there are three established subtypes of the disease: FGD 1, FGD2 and FGD3 corresponding to mutations in the Melanocortin 2 receptor MC2R (25%), Melanocortin 2 receptor accessory protein MRAP (20%), and Steroidogenic acute regulatory protein STAR (5–10%) respectively. Together, mutations in these 3 genes account for approximately half of cases. Whole exome sequencing in patients negative for MC2R, MRAP and STAR mutations, identified mutations in minichromosome maintenance 4 MCM4, nicotinamide nucleotide transhydrogenase NNT, thioredoxin reductase 2 TXNRD2, cytochrome p450scc CYP11A 1, and sphingosine 1-phosphate lyase SGPL1 accounting for a further 10% of FGD. These novel genes have linked replicative and oxidative stress and altered redox potential as a mechanism of adrenocortical damage. However, a genetic diagnosis is still unclear in about 40% of cases. We describe here an updated list of FGD genes and provide a description of relevant mouse models that, despite some being flawed, have been precious allies in the understanding of FGD pathobiology.